Three new South American species of Callianthe (Malveae, Malvoideae, Malvaceae) from Atlantic Forest and a new combination - Grings, Martin; Boldrini, Ilsi Iob (Phytotaxa, 2020)
Three new species of Callianthe (Malvaceae) from southern Brazil and northeastern Argentina are described, and illustrated: C. flava, C. maritima, and C. sulcatarinensis. Morphological descriptions, distribution maps, photographs, ecological notes, and a table comparing these species to two morphologically similar species, C. amoena and C. muelleri-friderici, are presented. Two of the three newly-described species, C. maritima and C. sulcatarinensis, so far are considered endemic and according to IUCN criteria, fit into the categories Endangered (EN) and Vulnerable (VU), respectively. A new combination C. costicalyx, based on Abutilon costicalyx, also is proposed.